The diagnostic and therapeutic challenges of Spontaneous Bacterial Peritonitis in a low income country: A case report - J.R. Nkeck , S. F Fru., A. Chiabi, Aurelie T. Sibetcheu, F. T. A. Endomba, (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: Spontaneous bacterial peritonitis is an uncommon condition. It has a non-specific clinical presentation which leading sometimes to an unnecessary laparotomy especially in a low income country.Case presentation: We received a 19-months old child, with an unremarkable past medical history, admitted in our service for a 2-day history of abdominal distension and fever. She presented with guarding and abdominal tenderness. Abdominal ultrasound revealed a peritoneal effusion and signs of intestinal occlusion without obstacle to peristalsis. A blood culture revealed Streptococcus sp as etiology and we made a diagnosis of spontaneous bacterial peritonitis. The patient recovered after medical treatment.Conclusion: Spontaneous bacterial peritonitis is a possible diagnosis that clinicians should bear in mind during investigation of an acute abdomen. Accurate initial diagnosis can avert unnecessary surgery, since treatment is medical.